Pengaruh Media Sosial Terhadap Cyberbullying Pada Remaja: Literature Review - Ismiray, Anugrah Ragil; Rahayu, Sri; Fajarini, Melati (Universitas Aisyah Pringsewu (UAP) Lampung, 2022)
Background: The social media has become the means for adolescents to interact with others, however, it may also be the means to several negative activities such as cyberbullying. These issue are important as it affecting adolescent’s health and there is a growing literature about these topics. Aim: This study aims to gather and analyze articles related to the influence of social media on cyberbullying in adolescents. Method: A literature search for articles published since the last 5 years from three databases, namely: Google Scholar, Portal Garuda, and DOAJ was conducted. A total of 1582 articles were screened and three articles were chosen following the PRISMA flowchart guidelines. Results: The literature show that social media effecting cyberbullying among adolescents, especially on Facebook. Conclusion: Social media influence cyberbullying, and teenagers who use social media more often will be more at risk of cyberbullying. Inititatives to improve adolescent health outcomes by learning positive usage of social media needs to be established. Further research related to efforts to reduce cyberbullying also needs to be done.